Occupational Therapy interventions for Activities of Daily Living in cancer Palliative Care: integrative review (Research, Society and Development, 2023)
Aim: to analyze Occupational Therapy interventions to improve participation in Activities of Daily Living of patients in cancer palliative care. Methods: integrative review, with a descriptive statistical analysis. Results were discussed in the categories “assessed aspects”, “identified problems” and “proposed interventions”, based on the International Classification of Functioning, Disability and Health. Results: the assessed aspects included required abilities and quality of participation. The most frequent problems were participation restrictions, body function impairments and environmental barriers. The interventions were the recovery and compensation of physical and cognitive body functions, and symptom control; promotion of participation, change of routine and habits, and environmental adaptation. Conclusion: The Occupational Therapy interventions were focused on the participation in Activities of Daily Living during all phases of the disease, through the recovery of body functions, or the adaptation of activity structure and environmental factors. Final considerations: this review adds an intervention profile for the maintenance of the participation and autonomy of patients in Palliative Care, the main goal of the approach, and strengthens the relevance of Occupational Therapy in healthcare teams.